Effect of different reverse osmosis water filters on fluoride content of drinking water - Mahesh Ravindra Khairnar; Vardhaman Mulchand Jain; Umesh Wadgave; Rohit Ishwar Dhole; Sandeep J Patil; Swapnil Ramchandra Chopade (Wolters Kluwer Medknow Publications, 2018)
Background: Reverse osmosis (RO) technology is an efficient method of reducing organic and inorganic contaminants of drinking water. It regulates the fluoride concentration in drinking water which influences the burden of dental caries and dental fluorosis in the general population. This study was designed with an aim to assess the effect of different RO water filters on fluoride content of drinking water. Materials and Methods: Ten different RO water filters available in the local market of Dhule city, Maharashtra, India, were tested in this study. Samples of filtered and nonfiltered tap water were collected from these RO filters installed in ten different households in the same area in Dhule city on three successive days, and fluoride analysis was done using fluoride ion selective electrode. Results: The amount of fluoride removed by different RO purification systems varied from 0.270 to 0.457 ppm (50.37%-84.62%). RO filters with total dissolved solid (TDS) controller showed more fluoride removal capacity (mean, 0.41 ppm) as compared to filters without TDS controller (mean, 0.36 ppm) (P > 0.05). Conclusion: RO is an effective defluoridation method. However, considering the beneficial effect of fluorides in reducing dental caries, when drinking water is subjected to water purification systems that reduce fluoride significantly below the optimal level, fluoride supplementation may be necessary.